2021
DOI: 10.22487/j24428744.2021.v7.i1.15257
|View full text |Cite
|
Sign up to set email alerts
|

Screening Bioactivity of Kersen Fruits (Muntingia calabura L.) as a Sunscreens Candidate

Abstract: Kersen (Muntingia calabura L) fruits have the potential to be used as an active ingredient in sunscreens because of phenolic and flavonoid content that can absorb UV rays. This study aims to determine the percentage of erythema/pigmentation transmission and SPF value as parameters for sunscreen activity.  Kersen fruits were extracted by maceration using 96% ethanol. The ethanol extract of Kersen Fruits was also fractionated to separate the components of the active compounds based on the polarity level using n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 4 publications
1
13
0
1
Order By: Relevance
“…The tests carried out in this study used various antioxidant testing methods, namely hydroxyl radicals, nitric oxide, β-carotene bleaching, and iron chelating agents. According to [8,19], the process of neutralizing free radicals with antioxidants is based on the presence of a hydrogen atom transfer reaction (HAT) and single electron transfer (SET) so that it can neutralize free radicals by two critical mechanisms, namely first, the presence of chain termination by primary antioxidants that can donate electrons to free radicals. Meanwhile, the second mechanism is removing the initiator of the ROS/RNS species by breaking the chain catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests carried out in this study used various antioxidant testing methods, namely hydroxyl radicals, nitric oxide, β-carotene bleaching, and iron chelating agents. According to [8,19], the process of neutralizing free radicals with antioxidants is based on the presence of a hydrogen atom transfer reaction (HAT) and single electron transfer (SET) so that it can neutralize free radicals by two critical mechanisms, namely first, the presence of chain termination by primary antioxidants that can donate electrons to free radicals. Meanwhile, the second mechanism is removing the initiator of the ROS/RNS species by breaking the chain catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…One of the plants that have the potential as an antioxidant is kersen fruit. Kersen (Muntingia calabura L.) is a plant that has an antioxidant effect [8,9]. Previous research has shown that kersen contains phenols and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent inhibition (%) of each sample can be calculated based on equation 1. % =[(Ao-As)/Ao]x 100% …………………………………………………………………………… (1) where AO is the negative control absorbance and As is the extract/standard absorbance.…”
Section: Iron Chelating Assaymentioning
confidence: 99%
“…Free radicals are molecules that do not have an electron pair in their outer orbital. Increased exposure to free radicals in the body is a significant factor in the increase in sufferers of degenerative diseases such as Alzheimer's, cancer, diabetes mellitus, Parkinson's, and several other degenerative diseases [1]. In general, exposure to minimal amounts of free radicals can be stabilized by endogenous antioxidants such as superoxide dismutase, glutathione peroxidase, glutathione reductase, glucose-6-phosphate 2nd International Conference on Tropical Wetland Biodiversity and Conservation IOP Conf.…”
Section: Introductionmentioning
confidence: 99%